Rejection of Accident Insurance Claims by Insurance Companies - Samudera, Berto Tegar (Universitas Wijaya Kusuma Surabaya, 2021)
Insurance is a form of compensation for the occurrence of uncertain risks and the delegation of responsibility to bear those risks. The event of this risk is uncertain because it depends on uncertainty. The transfer of risk is carried out by making an insurance agreement or insurance agreement. The first party is usually referred to as the insured. The second is the party willing to accept the risk of the first party by accepting a payment called a premium. Risk takers are often referred to as insurance companies. The research method used in this study uses a legal approach research method (statute approach) and a conceptual approach (conceptual approach). Based on the results of this study, the researcher states that the basis or cause of the rejection of an insurance agreement is because the insurance agreement is a conditional agreement, where the insurer only bears the loss suffered by the insured party following the terms of the event that resulted in the loss to the insured as agreed, by the parties in the insurance agreement. Or the insured party does not carry out its obligations to pay premiums to the insurer. The legal remedy that the insured party can take if the insurer rejects the claim is to file a lawsuit at the local District Court, as regulated in Article 23 of Law no. 8 of 1999. It can be completed through the BMAI institution.Keywords: Insurance, Claim, Dispute Resolution.